1985
DOI: 10.1016/s0735-1097(85)80089-9
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of regional myocardial blood flow with N-13 ammonia and positron-emission tomography in intact dogs

Abstract: N-13 ammonia mimics certain properties of microspheres. It rapidly clears from blood into myocardium where it becomes fixed in proportion to myocardial blood flow. Used with positron emission tomography as a means for quantifying in vivo myocardial indicator concentrations, N-13 ammonia may be useful for noninvasive determination of myocardial blood flow with the arterial reference sampling technique. This possibility was examined in 27 experiments in 10 chronically instrumented dogs at control, high and low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(31 citation statements)
references
References 18 publications
2
29
0
Order By: Relevance
“…Positron-emitting radiotracers have decay characteristics that permit quantification of regional myocardial activity in vivo (12). Regional myocardial perfusion can be estimated using N-13 ammonia or Rb-82 by direct measurement of tracer uptake (13)(14)(15)(16). Schelbert et al have previously demonstrated that uptake ofN-13 ammonia is linearly related to perfusion determined by radioactive microspheres from 0.5 to 3.0 times normal resting flow (13).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Positron-emitting radiotracers have decay characteristics that permit quantification of regional myocardial activity in vivo (12). Regional myocardial perfusion can be estimated using N-13 ammonia or Rb-82 by direct measurement of tracer uptake (13)(14)(15)(16). Schelbert et al have previously demonstrated that uptake ofN-13 ammonia is linearly related to perfusion determined by radioactive microspheres from 0.5 to 3.0 times normal resting flow (13).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…PET-measured MBF has shown excellent agreement with that measured by microsphere injection and invasive activity measurement (18)(19)(20)(21)(22). MBF can be measured by compartment modeling and estimation of rate constant values among tissue compartments ( Fig.…”
Section: Ffr Vs Mbfmentioning
confidence: 59%
“…The criteria for successful PTCA according to the NIH registry for coronary angioplasty has been a >20% increase in luminal diameter following the pro cedure (72). However, visual determination of percent narrowing is highly variable and coronary lesions are often eccentric (7,2). Recent studies have suggested that percent diameter narrowing may not accurately reflect coronary flow reserve since flow is affected by other dimensions such as length and absolute radius (1-3).…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tracers have decay characteristics that permit measurement of the uptake of tracers such as rubidium-82 (82Rb)and nitrogen-13 (I3N) ammonia to quantitatively assess regional perfusion (4)(5)(6)(7). Accordingly, the purpose of the current study is to determine the relation between changes in relative myo cardial perfusion reserve by positron emission tomog raphy, and coronary anatomy after percutaneous trans luminal coronary angioplasty.…”
mentioning
confidence: 99%